Sexual Dysfunction in Lesbian Women: A Systematic Review of the Literature - Sobecki-Rausch, Janelle Nicole; Brown, Oluwateniola; Gaupp, Christina Lewicky (Seminars in Reproductive Medicine, 2017)
Over the past two decades, a growing body of literature has demonstrated the prevalence of sexual dysfunction in heterosexual women. Few, if any, studies have investigated sexual problems specifically in women who identify as lesbian. The aim of this article is to systematically review data on sexual dysfunction in lesbian women. We performed a systematic review of the literature searching MEDLINE via Ovid, EMBASE, PsycINFO, Cochrane Database of Controlled Trials, SCI-EXPANDED, SSCI, CPCI-S, CPCI-SSH, and Web of Science from inception through March 2017. We included all studies assessing sexual dysfunction or sexual problems in lesbian women. Heterosexual, bisexual, and transsexual groups were excluded. Of the 1,822 articles identified, 20 articles met inclusion criteria, 1 of which was a population-based probability study. These studies included 16 cross-sectional studies, 1 case–control study, 1 qualitative interview study, and 1 review of the literature. Sexual dysfunction is prevalent in lesbian women and may differ from sexual dysfunction experienced by heterosexual women. Available data are limited by small convenience samples and varied outcome measures. Current validated surveys may be applicable to this subgroup. There is need for population-based studies with harmonized measures of sexual function to guide an evidence-based approach to sexual dysfunction in lesbian women.
Keywords: sexual dysfunction; sexual problems; lesbian; homosexual